Embedded through-section bars for the shear strengthening of RC beams - Dalfré, Gláucia (2012)
Embedded Through-Section (ETS) technique is a relatively recent shear strengthening strategy for reinforced concrete (RC) beams, and consists on opening holes across the beam thickness, with the desired inclinations, where bars are introduced and are bonded to the concrete substrate with adhesive materials. To assess the effectiveness of this technique, a comprehensive experimental program composed of 14 RC beams was carried out and the obtained results confirm the feasibility of the ETS method and reveal that: (i) inclined ETS strengthening bars were more effective than vertical ETS bars and the shear capacity of the beams has increased with the decrease of the spacing between bars; (ii) brittle shear failure was converted in ductile flexural failure and (iii) the contribution of the ETS strengthening bars for the beam shear resistance was limited by the concrete crushing or due to the yielding of the longitudinal reinforcement.